Qualitative Research Methods: do digital tools open promising trends? (Revista Lusófona de Educação, 2023)
Qualitative Research has gained greater scientific recognition in recent years, given the improvement of denser methodologies, more backed by knowledge from different areas of expertise. One of the factors that contributed to improving the quality of qualitative studies was incorporating a set of tools, most of them digital. Although these tools can support and reduce subjectivity, they must be aligned with the theoretical-conceptual-methodological frameworks of the research, which are the axes that give it coherence and cohesion. The researcher’s skills are fundamental to guarantee the integrity and ethics of the research construction process, from project formulation to disseminating results. In this context, in the case of qualitative data analysis, tools based on Artificial Intelligence (AI) can help researchers identify patterns and trends through a large volume of data, generate visualisations and syntheses and even offer suggestions for other questions or research areas. On the other hand, this dimension implies that the researcher develops digital and multimodal literacies. This essay is expected to discuss the challenges to overcome in developing and using accurate tools.Keywords: CAQDAS; artificial intelligence; digital methods.